High sensitivity c-reactive protein and homocysteine in patients with ischemic cerebrovascular disease - Marisol Peña Sánchez; Cesarina Lisselotte Torres Vázquez; Melany Betancourt Loza; Alina González-Quevedo Monteagudo; Marianela Arteche Prior; María Caridad Menéndez Saiz (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2024)
Foundation: High-sensitivity C-reactive protein and homocysteine seem to be related to ischemic cerebrovascular disease, but their findings on the risk and prognosis of this disease are controversial and inconclusive. Objective: to characterize high sensitivity C-reactive protein and homocysteine in patients with ischemic cerebrovascular disease. Methods: a descriptive and retrospective cross-sectional study was carried out in patients with ischemic cerebrovascular disease, admitted to the Stroke Service of the Neurology and Neurosurgery Institute between 2016 and 2019. Demographic variables, clinical manifestations, time of evolution, etiology and infarction location, risk factors. High-sensitivity C-reactive protein (cardiovascular risk) and homocysteine were quantified. Results: the means of C-reactive protein (7.0±8.3 mg/L) and homocysteine (17.1±7.3 µM) were high. Moderate and high cardiovascular risk occurred in equal proportions (46.8%). There were statistical differences in the relationship between cardiovascular risk and age (p=0.00); but neither the time of evolution nor the risk factors of the disease showed this behavior. Patients with high cardiovascular risk (hs-CRP >3 mg/L) and high homocysteine (>15 M), exhibited higher frequencies of atherothrombotic or cardioembolic etiologies. Conclusions: cardiovascular risk increases as the age of patients with ischemic cerebrovascular disease increases. Demographic, clinical and neurological characteristics did not show a relationship with high cardiovascular risk and high homocysteine values, although an associative trend of atherothrombotic etiology was found with increased high-sensitivity C-reactive protein and homocysteine.